IDENTIFIKASI PENYAKIT ANTRAKNOSA PADA CABAI MERAH (Capsicum annuum) DAN CABAI RAWIT (Capsicum frutescens) DI KELURAHAN AGROWISATA, KECAMATAN RUMBAI BARAT - Ibrahim, Roy; Alhaviz, Alhaviz; Safitri, Dian; Elfina, Yetti; Zafitra, Zafitra (Fruitset Sains : Jurnal Pertanian Agroteknologi, 2025)
Anthracnose is one of the main diseases in chili plants that causes a decrease in the quality and quantity of the harvest. This study aims to identify anthracnose disease in red chili (Capsicum annuum) and cayenne pepper (Capsicum frutescens) in Agrowisata Village, West Rumbai District. Observations were made through observation of symptoms in the field, pathogen isolation, and identification of colony and conidia morphology. The results of the observations showed the presence of typical anthracnose symptoms in the form of circular necrotic spots, dark sunken lesions, and rot on the fruit. Pathogen isolation on PDA media showed variations in colony color in both isolate sources, namely gray and peach in red chili and white and gray in cayenne pepper. Microscopic observations showed cylindrical conidia with both ends fusiform, according to the characteristics of Colletotrichum acutatum. Thus, it can be concluded that anthracnose disease in both types of chili is caused by C. acutatum. These findings are expected to be the basis for developing a more effective and sustainable disease control strategy for chili cultivation in the region.